2014
DOI: 10.3810/pgm.2014.09.2805
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Buprenorphine/Naloxone Dosing Impact on Treatment Duration, Resource Use and Costs in the Treatment of Opioid-Dependent Adults: A Retrospective Study of US Public and Private Health Care Claims

Abstract: Treatment with higher doses of buprenorphine/naloxone was associated with a longer time to treatment discontinuation, less resource use, and lower total medical costs despite higher pharmacy acquisition cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 2 publications
1
19
2
Order By: Relevance
“…In prior reports from clinical trials data, buprenorphine treatment retention varied from 20% at 52 weeks to 53% at 1 year and 25% at 2 years in more recent studies . One‐year retention rates reported from naturalistic studies are generally lower than in the VHA sample reported here, with 32–57% in small practice settings, just above 20% in a national program in Australia, and 42–45% in insurance claims data based studies from United States (about 20% retention after 3 years) . Comprehensive Statewide implementation of office based opioid treatment in Massachusetts in 2012 showed a 1‐year retention rate in buprenorphine OAT of 65%, the only report that approached retention rates reported here .…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In prior reports from clinical trials data, buprenorphine treatment retention varied from 20% at 52 weeks to 53% at 1 year and 25% at 2 years in more recent studies . One‐year retention rates reported from naturalistic studies are generally lower than in the VHA sample reported here, with 32–57% in small practice settings, just above 20% in a national program in Australia, and 42–45% in insurance claims data based studies from United States (about 20% retention after 3 years) . Comprehensive Statewide implementation of office based opioid treatment in Massachusetts in 2012 showed a 1‐year retention rate in buprenorphine OAT of 65%, the only report that approached retention rates reported here .…”
Section: Discussionmentioning
confidence: 51%
“…Several limitations deserve note. We lacked data on dose strength of buprenorphine, duration, and severity of OUD, type of opioid used or psychosocial factors, which can all influence treatment retention . We also did not have information on treatment interruptions, although we think such interruptions do not diminish the importance of evidence of sustained involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khemiri et al[46] conducted a retrospective cohort analysis of US beneficiaries with an opioid use disorder who were enrolled in a commercial healthcare insurance plan or in Medicaid, and who had a new buprenorphine/naloxone prescription with at least 1 refill. Individuals receiving low-dose BMT were compared to those receiving high-dose BMT.…”
Section: Resultsmentioning
confidence: 99%
“…Other outcomes of interest included lower criminal-justice-related costs associated with methadone maintenance therapy (MMT),[39] lower costs associated with buprenorphine/naloxone film versus tablets,[44, 45] and improved retention for high-dose versus low-dose buprenorphine/naloxone patients, with no significant increase in total direct healthcare costs. [46]…”
Section: Discussionmentioning
confidence: 99%